UPIN IPIN ANIMATION: THE MEDIA OF MALAYSIA'S IDENTITY POLITICS - Yasa, Gede Pasek Putra Adnyana; Putra, I Nyoman Darma; Pujaastawa, I B Gde; Julianto, I Nyoman Larry (E-Journal of Cultural Studies; Vol 16 No 3 (2023): Volume 16 Number 3 August 2023, 2023)
"Upin Ipin" animation is a popular children's film series in Indonesia, including Denpasar from 2010-2023. The Upin Ipin animation shows the background of a Malaysian village with its own culture, and the characters who play a role in it can represent the Malay-Malaysian identity and the various tribes that exist in Malaysia. The research used qualitative methods, and data were analyzed using discourse analysis theory and ideology theory. The results show that the issue of Malay-Malaysian identity plays a role in the production of Upin Ipin animation. The identity is visualized through the characters in the story, along with the environment that considers the socio-cultural background of the local Malaysian community. The construction of the environment, socio-cultural life, religion and culture, and language represent the Malaysian identity. This article contributes to the understanding that Upin Ipin animation is not just entertainment but a medium to introduce the Malay-Malaysian cultural identity. Keywords: animation, Upin Ipin, identity politics, Malaysia